Trend of Diversity Management and Organizational Performance Among Generation Y and Z Employees - Ridhayati Farid; Sri Cici Afrida Cahyati; Rizni Aulia Qadri; Sarfilianti Anggiani (Universitas Muhammadiyah Yogyakarta, 2025)
In today’s multigenerational workforce, managing diversity has become a strategic challenge for sustaining organizational performance, particularly in industrial zones such as Batam City. This study investigates the effect of diversity management on organizational performance among Generation Y and Z employees, with organizational climate as a mediating factor. A total of 280 employees aged 15–45 years participated as respondents, selected through purposive sampling to represent Generations Y and Z. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings show that diversity management significantly enhances organizational performance directly and indirectly through organizational climate. The results also confirm that diversity management positively shapes organizational climate, contributing to higher performance levels. These findings highlight the critical role of inclusive practices and supportive work climates in transforming generational diversity into innovation, engagement, and productivity. Theoretically, this study contributes by integrating diversity management and organizational climate frameworks into a unified model. Practically, it guides organizations in industrial clusters to implement inclusive strategies that optimize the potential of Generation Y and Z employees in achieving sustainable performance.